Medical resource use and cost of venlafaxine or tricyclic antidepressant therapy. Following selective serotonin reuptake inhibitor therapy for depression. - Griffiths, R; Sullivan, E; Frank, R; Strauss, M; Herbert, R; Clouse, J; Goldman, H (1999)
OBJECTIVE: An analysis of administrative and claims data was performed to compare the resource use and costs to a managed-care organisation of venlafaxine, a serotonin and norepinephrine reuptake inhibitor (SNRI), versus tricyclic antidepressant (TCA) therapy, after switching from a selective serotonin reuptake inhibitor (SSRI). DESIGN: One-year costs and frequencies of all medical services, and of services coded for depression, were compared between patients who received venlafaxine and TCA therapy as second-line therapy using bivariate and multivariate statistical analyses. SETTING: Data were obtained from 9 individual health plans with more than 1.1 million covered lives affiliated with a national managed-care organisation. PATIENTS AND PARTICIPANTS: Health plan members were included if they had a diagnosis of depression between July 1993 and February 1997. They also had to have at least 2 months of prescriptions for SSRI therapy followed by at least 2 months of venlafaxine or TCA therapy, and continuous enrollment in the plan from at least 6 months prior to 12 months following initiation of venlafaxine or TCA therapy. 188 patients who received venlafaxine and 172 patients who received TCAs met the inclusion criteria. MAIN OUTCOME MEASURES AND RESULTS: Patients who received TCAs were slightly but significantly older (43 vs 40 years) than venlafaxine recipients and, during 6 months prior to initiating therapy, had significantly higher mean costs coded for depression ($US451 vs $US311) and costs not coded for depression ($US4500 vs $US2090). Psychiatrists prescribed a significantly higher proportion of venlafaxine than TCA prescriptions (46.3 vs 25.0%). Prior to adjusting for confounding characteristics, during 12 months following initiation of therapy, mean depression-coded costs were significantly higher for venlafaxine than TCA recipients ($US1948 vs $US1396) and mean costs not coded for depression were significantly lower ($US4595 vs $US6677). Overall costs were not significantly different ($US6543 for venlafaxine vs $US8073 for TCA). Significant cost differences were observed with primary care physicians as initial prescribers of second-line therapy but not with psychiatrists. However, costs between the 2 groups were similar after adjusting for confounding variables, including prior 6-month costs and initial prescriber of second-line therapy. CONCLUSIONS: Payer costs are similar among patients receiving venlafaxine and TCA therapy following SSRI therapy. Higher costs of venlafaxine pharmacotherapy relative to TCA therapy may be offset by lower costs of other medical services. Differences in prescribing patterns and costs between primary care physicians and psychiatrists warrant further investigation.